Measurement of light output response in scintillator based neutron detectors using quasi-monoenergetic neutrons. (23rd July 2021) - Roy, A.S.; Banerjee, K.; Roy, P.; Seth, S.; Rana, T.K.; Sen, A.; Pandit, D.; Kundu, S.; Ghosh, T.K.; Mukherjee, G.; Manna, S.; Pandey, R.; et al.
Abstract: Conventional liquid scintillator (BC501A) and pulse shape discrimination capable plastic scintillator (EJ-299-33A) based detector of dimension; 5 inch diameter and 5 inch long, have been used to study pulse height response for quasi-monoenergetic neutrons of energy in the range 3 to 15 MeV generated using 7 Li(p, n) 7 Be reaction. Scintillation light output of plastic scintillator having pulse shape discrimination property is found to be 75% of the liquid scintillator at neutron energy (maximum recoil proton energy) of 3 MeV which improves with the increase in energy. Functional dependence of the scintillation light output in terms of recoil protons energy has been determined for the liquid and the plastic scintillator detectors for neutron energy in the range 3 to 15 MeV. This functional dependences were used in the Geant4 simulation to calculate the pulse height responses at several neutron energies.